Worldwide trends in prediabetes from 1985 to 2022: A bibliometric analysis using bibliometrix R-tool - Zhao, JingYi; Li, Min (Frontiers in Public Health, 2023)
Background: Prediabetes is a widespread disorder condition that is between normal serum glucose and diabetes. The aged and obese people experience a higher rate of prediabetes. Prediabetes is not only a risk factor for type 2 diabetes mellitus (t2dm), but also closely related to microvascular and macrovascular complications. Despite its importance, bibliometric analysis of Prediabetes is missing. The purpose of this study is to provide a comprehensive and visually appealing overview of the prediabetes research. Methods: First, the Web of Science(WOS) was enquired to collect all published articles associated to prediabetes, from 1985 to 2022. The R language was used to analyze the year of publication, author, country/region, institution, keywords, and citations. Finally, the network analysis is conducted using R package bibliometrix to evaluate the hotspots and development trends of prediabetes. Results: 9,714 research articles published from 1985 to 2022 were collected from WOS. The number of articles had experienced a sustained growth. Rathmann W was the most productive author with 71 articles. The Diabetes Care was the journal which published most articles (with 234 articles) on the subject of prediabetes and the Harvard University (with 290 articles) was the most active institution in this field. The United States contributed the most with 2,962 articles, followed by China with 893 articles. The top five clusters of keyword co-appearance network were “prediabetes”, “diabetes mellitus”, “glucose”, “insulin exercise”, and “oxidative stress”. The top three clusters of reference co-citation network were “Knowler. WC 2002”, “Tabak AG 2012”, “Matthews DR1985”. Conclusions: The combined use of WOS and R package bibliometrix enabled a robust bibliometric analysis of prediabetes papers, including evaluation of the emerging trends, hotspots, and collaboration. This study also allows us to validate our methodology, which can be used to better understand the field of prediabetes and promote international collaboration.